THE IMPORTANCE OF MUTUAL UNDERSTANDING AND RESPECT IN MULTICULTURAL SOCIETY - Nurwiati; Asrul, Taufiq Al-Islam; Sama, Abinus; Mitra, Robi; Sanduan, Varis Vadly (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
The implementation of Community Service (PKM) aims to provide a deep understanding to students who join the Damal Student Association (APMD) of Puncak Regency, Papua, in Jayapura City about the importance of development in the Papua region through living in mutual understanding in a multicultural society. The method of implementing this Community Service (PKM) is carried out directly by a team with two competent presenters with lecture techniques, discussions, and students providing opinions, and their respective arguments with problems that occur in the Papua region. Community Service (PKM) was carried out at the Damal Student Dormitory Building located in Prumnas 1, Waena, Heram District, Jayapura City, Papua Province on July 30, 2025. The results and implications of this community service (PKM) program show that students are enthusiastic in discussing Multicultural, Papua, and development. Development in Papua, in various aspects, is very much needed by its people, because it can improve their welfare. Papua does not only live one ethnicity, but has many ethnicities, both indigenous Papuans and non-Papuans. This region is increasingly multicultural, encompassing ethnicities, races, religions, cultures, and more. Therefore, the entire community needs to be educated on the importance of mutual understanding to minimize conflict and division within the community. Through this Community Service (PKM) program, all participants learned that respecting, honoring, and understanding cultural diversity can lead to regional progress, as